Atomistic Insights of Irreversible Li+ Intercalation in MnO2 Electrode. (25th November 2021) - He, Kun; Yuan, Yifei; Yao, Wentao; You, Kun; Dahbi, Mouad; Alami, Jones; Amine, Khalil; Shahbazian‐Yassar, Reza; Lu, Jun
Abstract: Tunnel‐structured MnO2 represents open‐framed electrode materials for reversible energy storage. Its wide application is limited by its poor cycling stability, whose structural origin is unclear. We tracked the structure evolution of β‐MnO2 upon Li + ion insertion/extraction by combining advanced in situ diagnostic tools at both electrode level (synchrotron X‐ray scattering) and single‐particle level (transmission electron microscopy). The instability is found to originate from a partially reversible phase transition between β‐MnO2 and orthorhombic LiMnO2 upon lithiation, causing cycling capacity decay. Moreover, the MnO2 /LiMnO2 interface exhibits multiple arrow‐headed disordered regions, which severely chop into the host and undermine its structural integrity. Our findings could account for the cycling instability of tunnel‐structured materials, based on which future strategies should focus on tuning the charge transport kinetics toward performance enhancement. Abstract : The lithiation front region of one β‐MnO2 nanowire analyzed by in situ TEM, where the MnO2 /LiMnO2 interface features arrow‐headed disordered regions, is disclosed with its atomic structure clearly captured. The findings have a bearing on MnO2 open‐framed electrode materials for reversible energy storage.